Factors Influencing Purchase Intention Through Tokopedia - Dewi Untari Ratna Ningsih; Dipa Mulia (Indonesian Journal of Business Analytics, 2025)
This study investigates factors influencing purchase intention on Tokopedia, focusing on brand image, e-service quality, online customer reviews/ratings, and the mediating role of e-trust. Using a quantitative method with PLS-SEM, data from 203 Tokopedia users were analyzed. Results show that brand image and online reviews/ratings do not directly affect purchase intention, while e-service quality has a significant positive impact. Brand image does not significantly influence e-trust, and e-trust itself does not significantly affect purchase intention. E-trust does not mediate the effects of brand image or e-service quality on purchase intention but significantly mediates the relationship between online reviews/ratings and purchase intention. These findings highlight the importance of service quality and credible customer reviews/rating in enhancing purchase intention.